Takeover premium and bidder performance in relation to market optimism and CEO relative compensation: Evidence from the Australian market - Luong, Hoa; Evans, John; Duong, Lien (2018)
This paper analyses the influence of market optimism and CEO relative compensation on takeover premiums and bidder performance. Consistent with the US and UK studies, the findings reveal that bid premiums are significantly higher if the deal initiated in high market optimism. The correlation between market optimism and bidder announcement returns is significantly positive, while its association with one year and two-year post announcement returns are in an inverse direction. We evidence the insignificant difference between bid premiums offered by CEOs who are paid a high relative compensation compared with that of deals undertaken by CEOs with low relative compensation. CEOs with high relative pay experience lower short-term returns around announcement and enjoys higher returns in one year, which is in sharp contrast to other markets. In the two years’ time, the outperforming effects become marginal and insignificant. Regarding the interaction between market optimism and CEO relative compensation, higher bid premiums are observed when CEOs with high relative pay take action in high optimism market, whereas higher short-term returns and lower long-term returns are presented if CEOs with low relative compensation process a deal in a strong market. The findings support a combination of neoclassical theory, misvaluation theory, and efficient contracting to be applied in the Australian context.